2020
DOI: 10.1007/s40259-020-00448-5
|View full text |Cite
|
Sign up to set email alerts
|

Approval of Itolizumab for COVID-19: A Premature Decision or Need of The Hour?

Abstract: Itolizumab is a first-in-class anti-CD6 monoclonal antibody that was initially developed for various cancers and was later developed and approved in India for treatment of moderate to severe chronic plaque psoriasis in 2013. This drug is now being re-purposed for COVID-19. The potential utility of itolizumab in COVID-19, based on its unique mechanism of action in ameliorating cytokine release syndrome (CRS), was proposed first in Cuba with approval of a single-arm clinical trial and expanded access use. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“… 11 Therefore, IL-6 blocking agents have been effectively used for the treatment of patients with hyper inflammatory states and also approaches intended at impeding this cytokine have been rapidly endeavored. 12 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Therefore, IL-6 blocking agents have been effectively used for the treatment of patients with hyper inflammatory states and also approaches intended at impeding this cytokine have been rapidly endeavored. 12 …”
Section: Introductionmentioning
confidence: 99%
“…A randomised trial of 30 patients with moderate and severe COVID‐19 recently concluded in India 15 . According to the initial data, none of the 20 patients assigned to itolizumab died, while 3 of the 10 individuals given usual care died 30 . While new trials are available, we speculate that the timely administration of itolizumab, guided by biomarkers, can interrupt the hyperinflammatory cascade and might prevent morbidity and mortality related to the cytokine release syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…15 According to the initial data, none of the 20 patients assigned to itolizumab died, while 3 of the 10 individuals given usual care died. 30 While new trials are available, we speculate that the timely administration of itolizumab, guided by biomarkers, can interrupt the hyperinflammatory cascade and might prevent morbidity and mortality related to the cytokine release syndrome. The safety and effectiveness of itolizumab in COVID-19 will be evaluated in a global, multinational phase III, randomised clinical trial (ClinicalTrials.gov number: NCT04605926).…”
Section: Discussionmentioning
confidence: 95%
“…Coronavirus disease (COVID- 19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was reported in Wuhan, Hubei Province, China on 17 November 2019, and was designated as a risk to public health on 30 January 2020 [1][2][3]. On 11 March 2020, the World Health Organization declared COVID-19 a pandemic [4].…”
Section: Introductionmentioning
confidence: 99%